A Comparative Analysis of Collaborative Problem-Solving Skills Between German and Chinese High School Students in Chemistry - Yike Ying; Rüdiger Tiemann (Education Sciences)
Collaborative problem-solving (CPS) skills are recognized as an essential aspect of 21st-century skills and STEM education. This study investigates the CPS skills of high school students from Germany and China within the context of chemistry. A total of 594 students, aged 15, were selected, comprising 249 females and 345 males. The German participants were drawn from five public high schools in Berlin, while the Chinese participants were selected from two high schools in Zhejiang. The assessment tool, developed based on the PISA frameworks and refined through pilot testing, was used to assess students’ CPS skills. The study found that Chinese students significantly outperformed their German counterparts in CPS tasks, exhibiting higher average scores and more consistent performance levels. Gender differences were also noted, with female students in both countries outperforming males. The analysis highlighted cultural influences on education, with the collectivist culture in China fostering stronger CPS skills compared to the individualistic tendencies in Germany. These findings suggest that cultural and gender differences need to be taken into account when developing and improving CPS skills. Future research will explore additional factors influencing CPS skills, such as student interest and motivation, to further understand and improve educational practices globally.